Experimental and computation assessment of thermomechanical effects during auxetic foam fabrication - DATA - Critchley, Richard; Smy, Victoria (Cranfield University, 2020)
Data used in this paper can be found in the attached thesis as an appendix. Link to file: https://eprints.soton.ac.uk/386209/
Keywords: 'auxetic foam'; 'COMSOL multiphysics software'; "negative Poisson's ratio"; 'Materials Engineering not elsewhere classified'